Gambaran Kedukaan pada Anak Sekolah Dasar dan Implikasinya Terhadap Layanan Bimbingan dan Konseling - Reka Ilmana Sifa (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Grief in children is a complex psychological experience that may significantly affect learning concentration, emotional regulation, and social interaction within the school environment. When not adequately addressed, unresolved grief can hinder children’s academic performance and psychosocial development. This study aimed to describe the level of grief experienced by elementary school students at SDN 3 Cikijing and to examine its implications for guidance and counseling services in schools. A quantitative descriptive research design was employed involving 90 students from grades IV to VI, consisting of 25 fourth-grade students, 30 fifth-grade students, and 35 sixth-grade students. Data were collected using the Grief Cognition Questionnaire for Children (GCQ-C), developed by Spuij et al. and adapted into Indonesian. The GCQ-C assesses negative cognitions and perceptions related to grief, providing a cognitive perspective on children’s bereavement experiences. The results indicated that 66.66% of students experienced a moderate level of grief, 17.77% experienced a high level of grief, and 15.55% experienced a low level of grief. Additionally, two students with the highest GCQ-C scores were identified as special cases for further analysis. The predominance of moderate grief suggests that although most students do not exhibit severe grief symptoms, they still face difficulties in managing negative thoughts and emotions associated with loss, which may influence their academic engagement and social relationships. These findings highlight the need for both preventive and curative guidance and counseling interventions in elementary schools. The study recommends the application of Person-Centered Expressive Arts Therapy (PCEAT) as an appropriate intervention, as it provides a safe and supportive space for children to express emotions through creative activities, enhance self-understanding, and foster psychological resilience during the grieving process.